EDUCATIONAL INTEGRATION ABROAD IN THE CONDITIONS OF MARITAL STATE - Miteva, Arina (Sworld-Us Conference proceedings, 2023)
The article is devoted to the forms and stages of formation of new educational institutions under martial law. The stages of integration of educational processes and the peculiarities of the choice of forms of education are separately highlighted, as well